Bridging the 4 trillion gap: UNCDF's catalytic role in financing sustainable development at the last mile - Pradeep Kurukulasuriya (University of Athens, Department of Economics, International Economics and Development Laboratory (IEDL), 2025)
This paper explores the catalytic role of the United Nations Capital Development Fund (UNCDF) in addressing the 4 trillion financing gap for the Sustainable Development Goals (SDGs), particularly in the world's 46 Least Developed Countries (LDCs). It argues that traditional development finance institutions (DFIs) and grant-making bodies have failed to mobilize sufficient capital in high-risk, underserved markets due to structural limitations and risk aversion. UNCDF's unique positioning - non-credit rated, impact-driven, and flexible in capital deployment - enables it to operate in frontier markets where others cannot. Through instruments such as blended finance, local currency loans, guarantees, and performance-based payments, UNCDF demonstrates how targeted, concessional investments can unlock domestic capital, crowd in private finance, and build resilient financial ecosystems. Case studies from Tanzania, Afghanistan, Zimbabwe, Rwanda, and Peru illustrate UNCDF's market-creating function and its capacity to serve the "missing middle" in development finance. The paper concludes by advocating for a recalibration of global risk models and a scaling of UNCDF's approach to transform fiscal constraints into engines of inclusive and sustainable growth.
Keywords: F35; G23; O16; O19; Q01; H81; 330; Blended Finance; Development Finance Architecture; Least Developed Countries (LDCs); Catalytic Capital; Financial Inclusion and Resilience